(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article studies the bibliographic indexes posted by Amir Temur and his descendant. The article also examines the issues of literature search, selection, placement of literature in these scientific and auxiliary indexes. The authors of the article determine that the compilers of indexes on the history of this period set a noble goal: to achieve complete inclusion of publications on this period.